Cognitive impairment in older patients undergoing colorectal surgery. Issue 1 (February 2018) - Hewitt, Jonathan; Marke, Margaret; Honeyman, Calum; Huf, Simon; Lai, Aida; Dong, Anni; Wright, Tom; Blake, Sarah; Fallaize, Rebecca; Hughes, Jane L; Pearce, Lyndsay; McCarthy, Kathryn
Background: With increasing numbers of older people being referred for elective colorectal surgery, cognitive impairment is likely to be present and affect many aspects of the surgical pathway. This study is aimed to determine the prevalence of cognitive impairment and assess it against surgical outcomes. Methods: The Montreal Cognitive Assessment (MoCA) was carried out in patients aged more than 65 years. We recorded demographic information. Data were collected on length of hospital stay, complications and 30-day mortality. Results: There were 101 patients assessed, median age was 74 years (interquartile range = 68–80), 54 (53.5%) were women. In total, 58 people (57.4%) 'failed' the Montreal Cognitive Assessment test (score ≤ 25). There were two deaths (3.4%) within 30 days of surgery in the abnormal Montreal Cognitive Assessment group and none in the normal group. Twenty-nine (28.7%) people experienced a complication. The percentage of patients with complications was higher in the group with normal Montreal Cognitive Assessment (41.9%) than abnormal Montreal Cognitive Assessment (19.9%) ( p = 0.01) and the severity of those complications were greater (chi-squared for trend p = 0.01). The length of stay was longer in people with an abnormal Montreal Cognitive Assessment (mean 8.1 days vs. 5.8 days, p = 0.03). Conclusion: Cognitive impairment was common, which has implications for informed consent. Cognitive impairment was associated with less postoperative complications but a longer length of hospital stay.